Excitation model of pacemaker cardiomyocytes of cardiac conduction system; Journal of Physics: Conference Series; Vol. 643 : Saint-Petersburg OPEN on Optoelectronics, Photonics, Engineering and Nanostructures (SPbOPEN2015) - Grigoriev M. G. Mikhail Georgievich (2015, 2015)
Title screen